Estudo das relações de trabalho e de impacto social nas operações em serviços de venda direta na região Centro Sul do Estado do Paraná - Cieslak, Marcos (2019)
ABSTRACT This research aims to promote an appreciation survey associating the direct and indirect contributions that the Local Productive Arrangement of União da Vitória (PR) and Porto União (SC). Also known as APL of Wood, presented to the local and regional development, especially in what concerns the associative organization and dissemination of the vocational productive identity of these two counties, highlighting the efforts made by public and private agents, especially in the consolidation of the local identity as a prominent pole in the national scenario, which carried out a series of events where they sought to expand markets, obtain technology and knowledge, as well as developing in synergetic ways synergetic to obtain common benefits. However, a series of factors, both external and internal, eventually caused this successful productive arrangement to lose its strength, simply running out of activity. As a methodological procedure it was initiated by bibliographical surveys, in research already carried out in this case, it was followed by a series of searches in several national and international productions, aiming to provide subsidies to this research, which is characterized by being descriptive once which reports unpublished facts of this APL, and a case study, since it sought to give depth to the situations raised here. For this, the study counted on the application of semi structured, interviews directed to the idealizers and executors of these collective actions, adding to local narratives, in order to provide qualitative analyzes on what this organization represented to the local development and the reasons for its current. It is concluded that, despite not presenting a linear process, the fact of promoting strategies and undertaking activities, from fairs, business roundtables, international missions, training among others, provided opportunities that would never have been obtained had they not been achieved in set.